Analisis Pengaruh Good Governance Bisnis Syariah, Ukuran Perusahaan, dan Struktur Modal terhadap Kinerja Perbankan Syariah: (Studi pada Bank Umum Syariah di Indonesia Periode 2012-2017) - Kurniya Wahyulaili; Novi Puspitasari; Marmono Singgih (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2018)
The aims of this study is to analyze the financial performance of general Islamic banks in Indonesia with maqashid sharia approach in terms of individual educational goals, the creation of justice, and the achievement of prosperity during the years 2012-2017. In addition, the aims of this study is to examine and analyze the factors that influence the determination of maqashid sharia in general Islamic banks companies in Indonesia in the period 2012-2017. The method used in the research is explanatory research. Variables used in this research consist of independent variable and dependent variable. The independent variables of this study are Good Governance Bisnis Syariah (GGBS), company size (SIZE), and capital structure (CS). The dependent variable of this study is Sharia Maqashid Index (SMI). The sample was chosen by using purposive sampling method and obtained the sample member as many as 9 companies of general shariah banks. Based on the results of this study with the t test shows that Good Governance Bisnis Syariah (GGBS) have negative effect to maqashid shariah. Meanwhile, company size variables have positive effect on maqashid shariah and variable of capital structure does not affect the achievement of maqashid shariah approach at general Islamic banks in Indonesia.